2020
DOI: 10.1038/s41419-020-03039-y
|View full text |Cite
|
Sign up to set email alerts
|

SPATS2, negatively regulated by miR-145-5p, promotes hepatocellular carcinoma progression through regulating cell cycle

Abstract: Spermatogenesis associated serine rich 2 (SPATS2) has been reported to contribute to the tumorigenesis of multiple malignancies. The molecular function of SPATS2 in hepatocellular carcinoma (HCC) is still not fully understood. In this study, we aimed to investigate the expression pattern and function roles of SPATS2 in HCC. The regulation of SPATS2 expression was also explored. We found that SPATS2 was highly expressed in HCC tissues in comparison with that in adjacent normal tissues. High expression of SPATS2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“… 26 miR-145 was also reported to regulate hepatocellular carcinoma progression and proliferation of epithelial ovarian cancer by targeting SPATS2 and SMAD4. 27 , 28 In order to reveal the relationship between miR-145 and ARF6 in HCC, some further experiments were implemented. ARF6 was subsequently predicted to be a downstream target gene of miR-145 by four different miRNA targeting prediction tools, and the targeting relationship was confirmed through dual-luciferase reporter assay.…”
Section: Discussionmentioning
confidence: 99%
“… 26 miR-145 was also reported to regulate hepatocellular carcinoma progression and proliferation of epithelial ovarian cancer by targeting SPATS2 and SMAD4. 27 , 28 In order to reveal the relationship between miR-145 and ARF6 in HCC, some further experiments were implemented. ARF6 was subsequently predicted to be a downstream target gene of miR-145 by four different miRNA targeting prediction tools, and the targeting relationship was confirmed through dual-luciferase reporter assay.…”
Section: Discussionmentioning
confidence: 99%
“…In liver cancer, it is highly expressed and could predict poor prognosis [ 6 ]. A recent study indicated that SPATS2 promotes hepatocellular carcinoma progression by regulating the cell cycle [ 7 ]. Additionally, SPATS2 serves as a target transcript of the small nucleolar RNA hostgene5 SNHG5 in colorectal cancer cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, miR-30a-5p can inhibit glycolysis and increase sensitivity to sorafenib through targeting CLCF1 in HCC, indicating modulating the expression level of miR-30a-5p has a promising therapeutic effect on HCC patients ( Zhang et al, 2020 ). Meanwhile, miR-145-5p can promote tumor progression by inhibiting SPATS2 ( Dong et al, 2020 ). In view of this research progress, miRNAs attract increasing research interest as potential targets in HCC diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%